Space vector PWM of three-phase inverter with MPPT for photovoltaic system. Issue 4 (2nd October 2021) - Wageh, Mostafa; Dabour, Sherif M.; Mostafa, R. M.; Ghalib, M. A.
ABSTRACT: This study introduces a photoelectric (PV) system based on the maximum power point tracking (MPPT) technique, which is performed by the perturb and observe P&O method. This algorithm is chosen due to its ability to withstand any difference in parameters and high efficiency. The interleaved boost converter characteristics are controlled using maximum power point tracking (MPPT), and Space vector modulation (SVPWM) is the control technique used to control the three-phase voltage source converter. In order to measure the overall performance of the system, simulations are performed in the MATLAB/Simulink environment.